Investigation of aerodynamic performance and operational optimization of wing sails at varying spacings - Zhang, Rui; Huang, Lianzhong; Peng, Guisheng; Ruan, Zhang; Ma, Ranqi; Wang, Kai; Cao, Jianlin; Wu, Jianyi; Li, Xiaowu (Ocean engineering, 2025)
The aerodynamic performance of sails determines the effectiveness of wind-assisted propulsion, with spacing being a key factor in sail interaction and thrust contribution. Investigating the aerodynamic performance and optimization of operation modes for sails under varying spacing will guide ship energy savings and emission reduction. The aerodynamic characteristics of crescent sails within 0°–60° angle of attack (AOA) range are systematically analyzed using a three-dimensional computational fluid dynamics (CFD) method validated by experiments. Based on the CFD results, an optimization procedure for the AOA under varying spacing is developed by integrating a surrogate model with a genetic algorithm. The variation of thrust coefficient (CT) and Energy Efficiency Design Index (EEDI) are examined. Specifically, desynchronized operation indicated a substantial advantage in enhancing the CT over synchronized operation; however, the improvement potential decreases with increasing spacing, from 12.6 % to 1.6 %. Meanwhile, the improvements in EEDI range from 1.7 % to 13.7 % on a 300,000-ton tanker. In the synchronized operation, the sail interaction effect is directly proportional to AOA and inversely proportional to spacing. In desynchronized operation, the optimized AOA configuration enables more wind energy to reach the downstream sail, which effectively enhances its thrust and hence the performance of the whole system. •The wing sails interaction is investigated with varing sapcing by using CFD codes.•The AOAs are optimized using a joint CFD, surrogate model and GA procedure.•Interaction is proportional to AOA in synchronization and inversely to spacing.•The improvement potential of system thrust is inversely proportional to spacing.•The EEDI improvements of optimal operation is 1.7 %–13.7 % in a VLCC.